Effect of reminiscence group therapy on depression, self-esteem and loneliness among elderly women residing in old age home - Sahu, Ipsita; Mohanty, Sailabala; Pahantasingh, Suchismita (International Journal of Research in Medical Sciences, 2019)
Background: Elderly women residing in old age home requires greater adaptability. Prevalence of depression, low self-esteem and feelings of loneliness are more among them. RGT has proven as a most effective alternative intervention especially for elderly at minimizing these above outcomes. Therefore, the present study assessed the effect of RGT on depression, self-esteem and loneliness among elderly women residing in old age home. Methods: Quantitative Research approach and quasi- experimental design was adopted. A total of 50 elderly women aged ³60yrs residing in Nirmal Hriday, Missionaries of charity old age home, Bhubaneswar were selected for experimental (N=25) and control (N=25) group by using purposive sampling. Baseline data were collected by using Socio demographic data Performa, Geriatric depression scale, Rosenberg self-esteem scale and UCLA loneliness scale after getting written informed consent from each participant. Total 3 biweekly reminiscence sessions for 45 minutes was held by dividing the experimental group into 4 groups. Results: Analysis revealed that after RGT, the experimental group showed that level of depression was decreased (before intervention 10.08±1.41 and after intervention 6.36±1.38), self-esteem was improved (before intervention 23.4±2.69 and after intervention 29.56±2.58) and loneliness was reduced (before intervention 36.92±4.57 and after intervention 20.96±5.09) significantly. There was a statistically significant difference found in depression, self-esteem and loneliness scores among experimental group as compared to control group (p<0.0001). Conclusions: On the findings of the study it was concluded that RGT yielded positive effects among elderly women residing in old age home.